Studies on carbonate ion transport through supported liquid membrane using primene JMT and tributyl phosphate - Gaikwad, Abaji G. (Separation Science and Technology, 2009)
A supported liquid membrane system consisting of source, receiving and membrane phases, in which mixed extractants were used in the membrane phase, was explored for the carbonate ion transport from source to receiving through membrane phase. Primary amine Primene JMT and TBP were used as extractants (carriers) in liquid membrane phase. Different experimental variables such as concentration of carbonate ion, carriers, alkali and hydrogen peroxide, stirring speed, etc have been investigated. Primary amine Primene JMT and TBP mixed carriers show the synergistic effect for the transport of carbonate ions through supported liquid membrane system. The stability of the supported liquid membrane system has been explored for 50 h. The pre-concentration of carbonate ions from dilute solutions were also demonstrated. The effect of different alkalis on the permeability coefficient of transport of carbonate ions through supported liquid membrane system has been investigated. The primary amine in combination with TBP shows more effective for the transport of carbonate ions through supported liquid membrane system in comparison with that of secondary and tertiary amines.
Keywords: carbonate ion; primary amine primene JMT; supported liquid membrane; synergistic effect; tributyl phosphate (TBP)

Transport of carbonate ions through supported liquid membrane by using Alamine 336 and trioctylphosphine oxide as carriers - Gaikwad, Abaji G. (Green Chemistry Letters and Reviews, 2011)
Transport studies were carried out for carbonate ions through supported liquid membrane (SLMs) by sing Alamine 336 and trioctylphosphine oxide (TOPO) as carriers. Experimental variables were investigated, such as concentration of carbonate ion (10(-5) to 4 x 10(-2) M), carriers (10(-5) to 10(-1) M), and alkali (0.01-0.5); and stirring speed (50-50 rpm) of bulk solutions. The use of combined carriers Alamine 336 and TOPO shows a synergic transport of carbonate ions. The stability of the SLM system in relation to the transport of carbonate ions has been studied. The enrichment of carbonate ions (10(-6) to 4 x 10(-2) M) from the dilute solution was explored. The different combinations of amines with TOPO show synergic permeability of the carbonate ions through SLM system.
Keywords: Alamine 336; carbonate ion; supported liquid membrane; synergic effect; trioctyl phosphine oxide (TOPO)